Climate Sensitivity Increases Under Higher CO2 Levels Due to Feedback Temperature Dependence. Issue 4 (20th February 2021) - Bloch‐Johnson, Jonah; Rugenstein, Maria; Stolpe, Martin B.; Rohrschneider, Tim; Zheng, Yiyu; Gregory, Jonathan M.
Abstract: Equilibrium climate sensitivity‐the equilibrium warming per CO2 doubling‐increases with CO2 concentration for 13 of 14 coupled general circulation models for 0.5–8 times the preindustrial concentration. In particular, the abrupt 4   × CO2 equilibrium warming is more than twice the 2   × CO2 warming. We identify three potential causes: nonlogarithmic forcing, feedback CO2 dependence, and feedback temperature dependence. Feedback temperature dependence explains at least half of the sensitivity increase, while feedback CO2 dependence explains a smaller share, and nonlogarithmic forcing decreases sensitivity in as many models as it increases it. Feedback temperature dependence is positive for 10 out of 14 models, primarily due to the longwave clear‐sky feedback, while cloud feedbacks drive particularly large sensitivity increases. Feedback temperature dependence increases the risk of extreme or runaway warming, and is estimated to cause six models to warm at least an additional 3K under 8   × CO2 . Plain Language Summary: Increasing CO2 reduces the rate at which energy leaves Earth, causing a net energy gain at its surface. The resulting warming increases the rate that energy leaves the planet. The planet stops warming once it regains balance. Studies usually assume that doubling atmospheric CO2 always produces the same eventual global temperature rise (called the "equilibrium climate sensitivity"), whatever the starting CO2 level. We show, on the contrary, that in nearly all the computer climate models we have examined, the extra warming for each doubling goes up as the CO2 level increases. In most models, the warmer the climate becomes, the more it has to warm in order to balance a further CO2 doubling because warming becomes less effective at rebalancing the flow of energy. This effect increases projections of warming, especially for scenarios of greatest CO2 increase. Key Points: Equilibrium warming per CO2 doubling increases with CO2 level for 13 of 14 climate models Positive feedback temperature dependence explains most of the sensitivity increase Nonlinear feedbacks increase the long‐term risk of extreme warming under high CO2 emissions